The harmonization of lending standards within banks through mandated loan-level transparency - Kang, Jung Koo; Loumioti, Maria; Wittenberg-Moerman, Regina (Journal of Accounting and Economics, 2021)
We explore whether the introduction of transparent reporting rules increases credit standard harmonization within a bank. We exploit the new loan-level reporting rules imposed on banks that borrow from the European Central Bank using repurchase agreements collateralized by their asset-backed securities. We compare credit terms of similar mortgages issued by a bank across a country's regions and find that harmonization increases following the adoption of the new reporting rules. Learning and regulatory scrutiny constitute mechanisms underlying this economic effect. We also show that harmonization leads to more favorable lending terms to borrowers and higher loan quality for banks. Overall, these findings suggest that transparent reporting rules incentivize banks to improve their internal decision-making and thereby reduce regional divergence in their credit standards.